Exploring MYC relevance to cancer biology from the perspective of cell competition. (June 2020) - Paglia, Simona; Sollazzo, Manuela; Di Giacomo, Simone; Strocchi, Silvia; Grifoni, Daniela
Abstract: Cancer has long been regarded and treated as a foreign body appearing by mistake inside a living organism. However, now we know that cancer cells communicate with neighbours, thereby creating modified environments able to support their unusual need for nutrients and space. Understanding the molecular basis of these bi-directional interactions is thus mandatory to approach the complex nature of cancer. Since their discovery, MYC proteins have been showing to regulate a steadily increasing number of processes impacting cell fitness, and are consistently found upregulated in almost all human tumours. Of interest, MYC takes part in cell competition, an evolutionarily conserved fitness comparison strategy aimed at detecting weakened cells, which are then committed to death, removed from the tissue and replaced by fitter neighbours. During physiological development, MYC-mediated cell competition is engaged to eliminate cells with suboptimal MYC levels, so as to guarantee selective growth of the fittest and proper homeostasis, while transformed cells expressing high levels of MYC coopt cell competition to subvert tissue constraints, ultimately disrupting homeostasis. Therefore, the interplay between cells with different MYC levels may result in opposite functional outcomes, depending on the nature of the players. In the present review, we describe the most recent findings on the role of MYC-mediated cell competition in different contexts, with a special emphasis on its impact on cancer initiation and progression. We also discuss the relevance of competition-associated cell death to cancer disease.